2023
DOI: 10.1002/psp4.12918
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative systems pharmacology of the eye: Tools and data for ocular QSP

Abstract: Good eyesight belongs to the most‐valued attributes of health, and diseases of the eye are a significant healthcare burden. Case numbers are expected to further increase in the next decades due to an aging society. The development of drugs in ophthalmology, however, is difficult due to limited accessibility of the eye, in terms of drug administration and in terms of sampling of tissues for drug pharmacokinetics (PKs) and pharmacodynamics (PDs). Ocular quantitative systems pharmacology models provide the opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 102 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, progress has been made in the development of PBPK and QSP models for ocular delivery, in part due to advancement in current understanding of ocular physiology and transport processes, that can be used to describe both systemic and ocular distribution of the drug. 75 A semimechanistic model was developed in rabbits to study ocular PK of various proteins administered IVT; the model was used to estimate half-life in retina, vitreous and aqueous humor in relation to protein size up to a hydrodynamic radius of 14 nm, which is the minimum radius for monomeric AAVs, and the authors suggested that the half-life in each compartment (retina, vitreous, and aqueous humor) could be geometrically scaled to humans. 76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, progress has been made in the development of PBPK and QSP models for ocular delivery, in part due to advancement in current understanding of ocular physiology and transport processes, that can be used to describe both systemic and ocular distribution of the drug. 75 A semimechanistic model was developed in rabbits to study ocular PK of various proteins administered IVT; the model was used to estimate half-life in retina, vitreous and aqueous humor in relation to protein size up to a hydrodynamic radius of 14 nm, which is the minimum radius for monomeric AAVs, and the authors suggested that the half-life in each compartment (retina, vitreous, and aqueous humor) could be geometrically scaled to humans. 76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
“…76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration. 78 Moreover, by coupling network systems biology models with complex QSP models, 75 one could study the drug effects on the downstream disease pathway.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Примером успешной диффузии являются липофильные препараты, способные пассивно проходить через эпителий роговицы, но затем задерживающиеся благодаря барьерным свойствам гидрофильной стромы. Монослой эндотелия роговицы выступает в качестве клеточного барьера между стромой и водянистой влагой и также может модулировать степень проникновения лекарственных препаратов [7,12]. Дальнейшее распределение препарата, преодолевшего роговицу, происходит в водянистой влаге.…”
Section: анатомические и физиологические барьеры снижающие биодоступн...unclassified
“…Многие местные лекарственные формы, содержащие НПВС, противоаллергические препараты, антибиотики, обладают в значительной степени гидрофильными свойствами, что ограничивает степень их проникновения в структуры глаза благодаря особенностям строения роговицы и конъюнктивы. Время местного воздействия препарата ограничивает оборот слезной пленки, что в итоге приводит к снижению концентрации действующего вещества в стекловидном теле и сетчатке [7].…”
Section: Introductionunclassified